Analisis Pembelajaran Sentra Balok Dalam Mengembangkan Fisik Motorik Anak Di TK Aisyiyah Bustanul Athfal 6 - Ersa Wahyuni; Yuniarti Yuniarti; Diana Diana (Institut Agama Islam Ngawi, 2026)
Motor development in early childhood is a crucial aspect that needs to be optimized through appropriate learning models. This research aims to describe the implementation of the block center (sentra balok) learning model in enhancing children's motor development at TK Aisyiyah Bustanul Athfal 6. The research design used is descriptive qualitative. Data collection techniques included direct observation, interviews with the principal and teachers, and documentation studies. The findings show that the implementation of the block center learning model is well-organized through three main stages: planning (Prosem, RPPM, RPPH, implementation covering four play pillars (environment, before, during, and after play), and evaluation. Supporting factors include adequate block media and spacious classrooms, while inhibiting factors include limited play time and a lack of play accessories. Overall, this model is effective in increasing children's focus and thinking skills.